Enhancing the interest of students and young people in classical poetry (Open Academia: Journal of Scholarly Research, 2024)
Classical poetry, with its rich emotional depth, timeless themes, and linguistic beauty, holds immense potential for inspiring young minds. However, in today's digital age, engaging students and young people with these works requires innovative approaches. This article explores strategies for enhancing the interest of modern youth in classical poetry by making it relevant to their experiences and accessible through contemporary methods. By drawing parallels between classical themes and present-day issues, incorporating technology, and promoting emotional connections, educators can revitalize appreciation for these literary treasures. Ultimately, fostering a deeper connection with classical poetry enriches personal growth, cultural understanding, and critical thinking.